Azole resistance in Aspergillus isolates by different types of patients and correlation with environment ‐ An Italian prospective multicentre study (ARiA study). Issue 5 (28th January 2021) - Prigitano, Anna; Esposto, Maria C.; Grancini, Anna; Biffi, Arianna; Innocenti, Patrizia; Cavanna, Caterina; Lallitto, Fabiola; Mollaschi, Eva Maria Giada; Bandettini, Roberto; Oltolini, Chiara; Passera, Marco; De Lorenzis, Gabriella; et al.
Abstract: Background: A wide range of frequency of azole‐resistance in A fumigatus in different patient populations worldwide was observed threatening to reduce therapeutic options. Objectives: Estimate the prevalence of azole‐resistance, investigate the molecular mechanisms of resistance, compare the genotypes of resistant clinical isolates with those from the surrounding environment. Methods: Aspergillus isolates were collected by seven Italian hospital microbiology laboratories. Strains were isolated from different clinical samples from unselected patients. The azole‐resistance was evaluated using screening test and microdilution EUCAST method. The molecular mechanism of resistance was performed sequencing the cyp51A gene. Resistant isolates were genotyped by microsatellite analysis and their profiles compared with those of azole‐resistant isolates from previous Italian studies. Results: 425 Aspergillus isolates from 367 patients were analysed. The azole‐resistance rates were 4.9% and 6.6% considering all Aspergillus spp. isolates and the A fumigatus sensu stricto, respectively. All resistant isolates except one were from a single hospital. Two rare azole‐resistant species were identified: A thermomutatus and A lentulus . The predominant resistance mechanism was TR34 /L98H. No correlation between the clinical resistant strains and environmental isolates from patients' home/work/ward was observed. The analysis of the molecular correlation between the resistant clinical strains collected in the present study and those of environmental and clinical origin collected in previous Italian studies reveals a progressive diversification of azole‐resistant genotypes starting from a founder azole‐resistant genotype. Conclusions: This study confirms the trend of azole‐resistance rate in Italy, showing a geographical difference. Data reinforce the importance of surveillance programmes to monitor the local epidemiological situation.